Endoscopic characterization of oropharyngeal dysphagia in patients with dementia - Sara Peranovic; Maryam Pourhassan; Bendix Labeit; Paul Muhle; Sonja Suntrup-Krueger; Tobias Warnecke; Rainer Dziewas; Ulrike Trampisch; Rainer Wirth; Gero Lueg (Frontiers in Aging)
ObjectiveDiagnosing and treating dysphagia in patients with dementia is challenging and few studies have been performed to characterize dysphagia based on Flexible Endoscopic Evaluation of Swallowing (FEES). Therefore, we aimed to characterize and compare the dysphagia pathologies in various stages and types of dementia.MethodsThis is a retrospective study of 107 hospitalized geriatric patients with dysphagia and Alzheimer’s dementia, Alzheimer’s dementia with moderate to severe cerebral vasculopathy (mixed dementia), and patients with dementia associated with Parkinson’s syndrome who underwent FEES. A standardized FEES protocol was used to characterize the dysphagia pathologies, including premature bolus spillage, delayed swallowing reflex and bolus residue as well as penetration and aspiration and the white-out intensity. The distribution of different dysphagia pathologies was cross-tabulated with χ2 statistics across different types of dementia.ResultsA comparative analysis of dysphagia pathologies across the three dementia types revealed a relatively mixed picture of various dysphagia findings in all dementia types. However, a significantly higher prevalence of bolus penetration and complex dysphagia, which was defined as presence of at least two major findings simultaneously within a patient, was seen in patients with Parkinson’s-related dementia compared to other forms of dementia. In general, residue was the most frequent finding in all types of dementia (78%–100%). In contrast, aspiration was the least prevalent finding with no significant variation between dementia types.ConclusionAlthough participants with Parkinson’s-related dementia exhibited minor specific findings, our study revealed no distinct endoscopic dysphagia pathologies across various types of dementia.